New teratological cases in cuckoo wasps, with synonymization of Oligogaster Soliman & Kimsey (Hymenoptera, Chrysididae) - Rosa, Paolo (Zootaxa, 2024)
Aberrations involving the metasoma in Hymenoptera are well-documented, with one notable teratological case being the fusion of metasomal terga, named symphysomery. This aberration, characterized by the fusion of the second and third terga, has been observed in various species groups of Hedychridium, spanning from Southern Africa to Central Asia. Similar aberrations were noted in Prochridium Linsenmaier from Mongolia and Anachrysis Krombein from Southern Africa. The monotypic genus Oligogaster Soliman & Kimsey is distinguished by two visible metasomal terga. However, the sole specimen of Oligogaster kimseyae Soliman, the type species of the genus, is here considered an aberrant specimen affected by symphysomery, exhibiting the fusion of the second and third metasomal terga. Consequently, Oligogaster Soliman & Kimsey is here synonymized with Hedychridium Abeille de Perrin.